Business law and the regulatory environment: concepts and cases - Metzger, Michael B.; Mallor, Jane P.; Barnes, James A.; Bowers, Thomas; Philips, Michael J. (Homewood, Illinois. Richard D. Irwin, Inc., 1986)
"In many chapters, current adopters will also notice an increased emphasis on the social forces that shape legal rules. Wherever feasible, we have attempted to identify both the historical factors that contributed to the evolution of the legal rules under discussion and the social function performed by those rules. We have done this because we believe that a complete understanding of the law requires an understanding of the origins, as well as the content, of legal rules. In addition to these changes in approach, this new edition has been reorganized in a variety of ways. The discussion of legal reasoning has been expanded and moved from Chapter 2 to Chapter 1 due to its obvious affinity with the opening chapter's expanded discussion of the nature of law. The chapters on agency law have been reorganized reduced in number from three to two. The previously separate chapters on landlord-tenant and real property have been combined because of their common intellectual heritage and because many of the important legal trends relating to transactions."
Includes appendixes and index.
English text.
Keywords: Business Law